The Use of Instagram Application as a Media Evaluation of Animal Excretion System Material in Biology Education Students - Nadia Dwi Cahyawati; Ervina Rinka Oktarivada; Kartikasari Nurbaiti; Zumrotul Salisa; Ghina Tsalatsatunnisa; Setiyo Prajoko (Indonesian Journal of Biology Education, 2021)
The implementation of Education Policy in the Emergency Period of the Spread of Corona Virus Disease (COVID-19) greatly affects the condition of education in Indonesia, therefore, educators are expected to develop certain activities that use social media in learning. Educators can actively use Instagram to stay connected with students. The use of Instagram by students is used as an evaluation medium related to animal excretory system material in Biology Education Students. The data analysis method used is qualitative descriptive method. Based on the research that has been done, it can be concluded that the use of media in learning is a very important element, knowledge will be more abstract if only conveyed through verbal language. This can be seen in the aspect of the Instagram application which is able to become an evaluation media with a percentage of 84%.